Investigation of wear in induction-heated AISI E 52100 steel bars under reciprocating motion. (1st January 2012) - Koga, Masatoshi; Santos, Edson Costa; Honda, Takashi; Kida, Katsuyuki; Shibukawa, Takuya
AISI E52100 steel (JIS SUJ2) is used in the manufacture of bearings and linear guides because of its high hardness and wear resistance under rolling contact. The life estimation methods for components working under rolling contact developed up to now were designed for bearings. In this study, fatigue testing under reciprocating motion was performed and based on the microstructure, wear track observation, electron backscattered diffraction (EBSD), hardness and retained austenite measurements, an evaluation method for linear guides is proposed. The results obtained from three different areas of the sample including wear tracks and non-damaged area are as follows: 1 there was little microstructure difference between the centre and the edge of the wear track 2 a clear difference of the retained austenite content at the wear track and at the non-damaged area could be observed, however the percentage within different areas inside the track was similar.